Evidence of chemical heterogeneity within lunar anorthosite parental magmas. (1st December 2019) - Pernet-Fisher, John F.; Deloule, Etienne; Joy, Katherine H.
Abstract: Lunar anorthosites are known for displaying a limited range of plagioclase An content (∼An 94 to 98). Here we demonstrate that plagioclase trace-element variations from Apollo ferroan anorthosites (FAN) samples (collected by the Apollo 15 and 16 missions) display more significant chemical heterogeneity (e.g., chondrite-normalized [La/Sm] 0.33–5.42) than previously reported. We report mineral (plagioclase, pyroxene, and olivine) major- and trace-element abundances for a suite of Apollo FAN samples, in addition to, anorthositic clasts within Apollo 16 regolith breccias. This suite of data extends the compositional range currently reported for Apollo anorthosites and for anorthositic clasts previously found within lunar meteorites. Petrological classifications of the regolith breccia clasts (e.g., anorthosite versus noritic anorthosites) cannot always be accurately assessed due to the limited size (<1 cm) these rock fragments, however, the overlap in chemistry with the FAN suite highlights a genetic link with the FAN bedrock source. This observation emphasizes the usefulness of clasts and mineral fragments within regolith breccias, offering important insights into potentially unsampled bedrock lithologies from the Apollo 16 landing site. Melts in equilibrium with plagioclase can be used to assess parental melt compositions of the lunar magma ocean (LMO), from which anorthosites are generally agreed to have crystallized. In general, melts in equilibrium with the anorthosites reported here display slight light rare earth (LREE) depletions to LREE enrichments ([La/Sm]CI 0.87–2.5). The observed range of LREE enrichments from this suite, together with variations in ratios of other incompatible trace-elements (e.g., Th/Sm = 0.002–0.19) cannot be accounted for by fractional crystallization alone. We propose that the observed trace-element enriched anorthosites are related to overturn processes in the lunar mantle. During mantle overturn, the act of exhuming deep mafic-rich cumulates to the base of the lunar crust will trigger decompression melting. These are likely to be small degree (<10%) partial melts, which are typically enriched in incompatible elements. Variable mixing between such melts, KREEP, and overlying plagioclase-saturated residual melts or plagioclase-rich lithologies will result in lunar anorthosites that display variable incompatible element enriched signatures. This is similar to the proposal of Floss et al. (1998) that suggested infiltration of local LMO magmas occurred by more evolved liquids through a process of metasomatism. By understanding the petrogenesis of these lunar anorthosites, we are able to constrain some of the complexities associated with the solidification of a magma ocean. This in turn, has important implications for understanding the timing and formation mechanisms of the Moon's crust.